2018
DOI: 10.1111/cen3.12477
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidelines for dimethyl fumarate

Abstract: A multicenter, randomized, double‐blind, placebo‐controlled, efficacy and safety study of BG00012 in participants from the Asia–Pacific region and other countries with relapsing–remitting multiple sclerosis (APEX), including Japan, established the efficacy of dimethyl fumarate (DMF) in preventing relapses and disease progression in patients with multiple sclerosis (MS). Consequently, in December 2016, DMF was approved as the second oral disease‐modifying drug for MS in Japan. However, the new Japanese guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Flushing accompanied by itching and burning sensations has an incidence of 22-38% based on previous clinical trials. 3,24 Natalizumab Two global phase III clinical trials; that is, the Natalizumab Safety and Efficacy in Relapsing-Remitting Multiple Sclerosis (AFFIRM) 25 and Safety and Efficacy of Natalizumab in Combination With Interferon Beta-1a in Patients With Relapsing-Remitting Multiple Sclerosis (SENTINEL) 26 studies, showed significant efficacy in reducing clinical relapse rates and risk of sustained progression of disability. Moderate-to-severe lymphopenia might increase PML risk, and it is recommended to obtain a complete blood count before the treatment and to monitor the lymphocyte count for, at least, every 3 months during the DMF treatment.…”
Section: Fingolimodmentioning
confidence: 99%
See 3 more Smart Citations
“…Flushing accompanied by itching and burning sensations has an incidence of 22-38% based on previous clinical trials. 3,24 Natalizumab Two global phase III clinical trials; that is, the Natalizumab Safety and Efficacy in Relapsing-Remitting Multiple Sclerosis (AFFIRM) 25 and Safety and Efficacy of Natalizumab in Combination With Interferon Beta-1a in Patients With Relapsing-Remitting Multiple Sclerosis (SENTINEL) 26 studies, showed significant efficacy in reducing clinical relapse rates and risk of sustained progression of disability. Moderate-to-severe lymphopenia might increase PML risk, and it is recommended to obtain a complete blood count before the treatment and to monitor the lymphocyte count for, at least, every 3 months during the DMF treatment.…”
Section: Fingolimodmentioning
confidence: 99%
“…2,4 Regarding effectiveness and longterm safety, the guidelines recommend initiation of treatment with the first-line approved drugs that are injectable. 3,24 Post-marketing data from Italy showed a better clinical and radiological outcome in treatment-na€ ıve patients (started DMF as first treatment) compared with patients who switched from other DMD to DMF. 3,24 Post-marketing data from Italy showed a better clinical and radiological outcome in treatment-na€ ıve patients (started DMF as first treatment) compared with patients who switched from other DMD to DMF.…”
Section: Positioning Of Each Dmd and Treatment Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent treatment advancements have led to the availability of numerous disease‐modifying therapies (DMTs) for RMS/RRMS. Many DMTs are approved for use in the US and/or EU by the United States Food and Drug Administration (FDA) and European Medicines Agency; however, only seven DMTs are currently available for RRMS in Japan: dimethyl fumarate, fingolimod, glatiramer acetate, interferon beta‐1a (IFNβ‐1a), interferon beta‐1b (IFNβ‐1b), natalizumab, and ofatumumab 9–11 . The 2017 treatment guidelines from the Japanese Society of Neurology recommend early introduction of a DMT in patients with RRMS to reduce/prevent irreversible disability progression over time 9 .…”
Section: Introductionmentioning
confidence: 99%